Slowed vertical saccades as a hallmark of hereditary spastic paraplegia type 7. Issue 10 (10th October 2019) - Milenkovic, Ivan; Klotz, Sigrid; Zulehner, Gudrun; Sycha, Thomas; Wiest, Gerald
Abstract: Anecdotal oculomotor disturbances have been described in spastic paraplegia type 7 (SPG7). We investigated oculomotor and vestibular dysfunction in five patients with genetically verified SPG7. All five patients exhibited significantly slower velocities of vertical saccades compared to controls, but significantly faster than in progressive supranuclear palsy, with upward saccades being particularly affected. Horizontal saccades, cerebellar oculomotor markers, and vestibuloocular reflex seem to be variably affected. Thus, albeit subclinical in some cases, slowing of the vertical saccades may belong to the phenotype of SPG7 and may serve as a valuable biomarker for differentiation from spastic ataxias and atypical parkinsonism.